Stress Monitoring of Civil and Mechanical Engineering Infrastructure - Brennan, Feargal P. (British Institute of Non-destructive Testing, 2007)
Structural Integrity Monitoring is a rapidly growing science and practice which promises in the future to measure and record every shudder and twitch within the lifetime of future structural components. Indeed, structures will undoubtedly possess nervous systems which will sense and instantly communicate loading and damage information; however, it is timely to stand back and consider what is required from such systems before we drown in yotta-bytes of monitored data. The electronics industry is rapidly developing clever wireless data transmission and more efficient storage methods, with increased sampling frequencies and multiplexing technologies which can distract even the most focused Civil or Mechanical Engineer. Stress measurement and monitoring is more complex than traditional NDT which considers defect and crack detection, but if understood properly can in some ways be much simpler and promises safer and better optimised structures. The paper reports several case studies of stress monitoring in Rail applications and of Steel Structures using Stress Memory Technology and will discuss how stress monitoring systems might be evaluated in terms of reliability and value.